Pelatihan Penyusunan Modul Kimia Berbasis Kearifan Lokal bagi Guru SMA di Sungai Penuh Jambi - Sanova, Aulia; Syahri, Wilda; Yusnidar, Yusnidar; Afrida, Afrida (Jurnal Pengabdian UNDIKMA, 2022)
This service program aims to provide knowledge and increase teacher competence in compiling teaching materials in modules based on local wisdom by integrating elements of the cultural habits of the local community. The methods were done by training with technical lectures, discussions, questions - answers, and assignments. This service program was attended by 12 science teachers at SMAN 2 Sungai Penuh. The evaluation form of this program was in the form of a response to the usefulness and impact obtained from the activity results through the distribution of questionnaires and using a question-and-answer method with qualitative descriptive techniques to determine the strategy for implementing the ethnoscience module in the classroom learning process. The results showed that the teacher understood and strongly agreed that ethnoscience was integrated into the lesson. Furthermore, the teacher could draft teaching materials containing local wisdom in learning modules.